Cucumis metuliferus reduces Meloidogyne incognita virulence against the Mi1.2 resistance gene in a tomato–melon rotation sequence. Issue 7 (16th January 2019) - Expósito, Alejandro; García, Sergi; Giné, Ariadna; Escudero, Nuria; Sorribas, Francisco Javier
Abstract: BACKGROUND: Susceptible tomato cv. Durinta, ungrafted or grafted onto cv. Aligator resistant rootstock, both followed by the susceptible melon cv. Paloma, ungrafted or grafted onto Cucumis metuliferus BGV11135, and in the reverse order, were cultivated from 2015 to 2017 in the same plots in a plastic greenhouse, infested or not with Meloidogyne incognita . For each crop, soil nematode densities, galling index, number of eggs per plant and crop yield were determined. Virulence selection was evaluated in pot experiments. RESULTS: In the tomato–melon rotation, nematode densities increased progressively for the grafted tomato, being higher than for ungrafted plants at the end of the study; this was not the case in the melon–tomato rotation. Grafted crops yielded more than ungrafted crops in the infested plots. Virulence against the Mi1.2 gene was detected, but not against C. metuliferus . Reproduction of M. incognita on the resistant tomato was ∼ 120% that on the susceptible cultivar after the first grafted tomato crop, but this decreased to just 25% at the end of the experiment. CONCLUSION: Alternating different resistant plant species suppresses nematode population growth rate and yield losses. Although this strategy does not prevent virulence selection, the level was reduced. © 2018 Society of Chemical Industry Abstract : Alternating crops of different resistant plant species suppresses nematode population growth rate and crop yield losses. Moreover, although this strategy does not prevent virulence selection, the resultant level of virulence is reduced.